PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN PENGAWAS TERHADAP MOTIVASI SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM (PU) KABUPATEN BATANG HARI JAMBI - Muhammad Oceano Fauzan; Fathiyah Fathiyah (Universitas Batanghari, 2017)
An organization was formed not only intended to produce the product. The resulting products of an organization can be a goods and service also can distinguish thoseorganizations with other organizations. While the perpetrators who carry out the work referred to the performance. The notion of performance in General can be said asthe magnitude of the contributions or the results of the work accomplished provided employees towards progress and development or organizational goals or organisation where he worked. This type of research is descriptive research and verifikatif with analysis tools in the form of path analysis (Path analysis). This research was conducted in the public works agency Batang Hari Jambi with a number of employees as many as 95 people as research samples. the results of hypothesis testing simultaneously between the variables (X 1), organization culture, leadership style (X 2), supervision (X 3), with a motivational variable (Y) shows that F calculate the significant level 9,669 0000. from the table above shows that the value of t count variable (Y) motivation is significant level 4,488 0000. because 0.000 H0 is rejected then the 0.05 < Hoaccepted (significant). The results show that partially motivated (Y) effect on performance (Z) on public works Districts Batanghari Jambi.Keywords: organizational culture, leadership style